Analisis Kesesuaian Capaian Pembelajaran dengan Bahan Ajar Teks Berita pada Buku Bahasa Indonesia Kelas XI di SMA Negeri 1 Percut Sei Tuan - Merry Natalia Gurning; Artika Fechriani Marpaung; Meylan Siahaan; Ruth Nila Sari Lubis; Trisnawati Hutagalung; Nurul Azizah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the suitability between learning outcomes and news text teaching materials contained in the Indonesian language textbook for grade XI students used at SMA Negeri 1 Percut Sei Tuan. Using a qualitative descriptive approach, this study examines the material structure, news text examples, and learning activities contained in the textbook, then compares them with the learning outcomes set in the Independent Curriculum. The results show that most of the teaching materials are aligned with competency requirements, particularly in understanding the structure and linguistic elements of news texts. The textbook provides relevant news text examples and learning activities that support students' understanding of news texts. However, some sections, such as in-depth analysis activities and text production exercises, still do not fully meet the standards expected in the Independent Curriculum. This indicates room for improvement in developing more comprehensive teaching materials. Therefore, enrichment of teaching materials is needed to optimize student competency achievement, as well as providing more applicable exercises to improve students' abilities in analyzing and producing news texts. Developing more in-depth teaching materials will improve the quality of learning and student competency achievement.